The Women’s Stress, Sleep, Physical Activity, And Pain Level During Pregnancy in The Covid Outbreak - Zengin Alpözgen, Ayşe; Günday, Çiçek; Polat, Basak; Evrendilek, Halenur; Erturk Uzunoglu, Gamze; Akuzum, Funda; Tahmaz, Tugce (Göbeklitepe Medical Science Journal, 2022)
COVID-19 pandemic may lead to changes in stress, sleep, physical activity (PA), and pain intensity related to the pregnancy. The study aimed to investigate the perceived stress, quality of sleep, PA, and pain intensity of pregnant women who were advised to stay at home as much as they could to provide isolation during the pandemic. The study included one hundred forty-nine pregnant women between April and May 2020. Demographics were recorded; Perceived-Stress Scale (PSS), Pittsburgh Sleep Quality Index (PSQI), International Physical Activity Questionnaire-Short Form (IPAQ-SF), and Numerical Pain Rating Scale (NPRS) were performed. Most participants (79.2%) were in social isolation for more than 21 days. Self-reported anxiety level was severe for 65.8% of participants. The mean PPS score (±SD) was 26.98±8.26, PSQI score was 6.14±2.87, IPAQ-SF score was 466.1±1421.28, and NPRS score was 4.42±2.65. When the participants were classified and compared according to the trimester, no statistical significance was found in PPS, PSQI, IPAQ-SF, and NPRS scores (p> 0.05). The correlation was low between PPS-PSQI scores (r=0.291, p?0.001); NPRS and PSQI scores (r=0.198, p=0.016). Pregnant women reported moderate stress level, poor sleep quality, very low PA level, and moderate pain intensity in the pandemic.